The effect of 8 weeks of aquatic and land exercise training on balance and proprioception of the ankle joint in children with diplegia cerebral palsy - Hamid Abbasi; Hossein Ghasemsharifi; Saeed Abedinzadeh; Reza Sharifatpour (Shahid Beheshti University, 2024)
Background and Purpose: Children with spastic cerebral palsy have many problems in terms of movement and balance. The crooked structure of children with spastic cerebral palsy disturbs their balance function. Due to the constant muscle tension in these people, a permanent spasm is seen in their flexor muscles. Together with other features of the disease, this leads to limited mobility for those affected. Recently, training in water and on land have become very popular in both sports and rehabilitation, especially for people with limited mobility. The aim of this study was to investigate the effects of a functional training protocol combining water and land exercises on the balance and proprioception of the lower limbs of children with cerebral palsy and diplegia.Materials and Methods: Thirty children with diplegia cerebral palsy were selected through available sampling and randomly divided into two equal groups of experimental (age, 9.33±1.63 years; height, 1.32±0.06 m; weight, 33.88±3.63 kg) and control group (age, 9.46±1.30 years; height, 1.30±0.05 m; weight, 32.04±3.52 kg). Subjects in the experimental group performed a training protocol on the ground including strength exercises, balance exercises and functional exercises and training protocol in water for 8 weeks and 4 sessions per week.  Before and after the training period static balance was evaluated by using the functional reaching test, the dynamic balance by using the time up and go test (TUG), and joint proprioceptive by measuring the angle of dorsiflexion. To statistically analyze the data, two-way repeated measures of ANOVA was used at a significant level of p≤0.05.Results: After 8 weeks of land and water combined training, there were significant improvements in the functional balance test (p<0.05) and ankle joint proprioception (p=0.001), as well as a significant reduction in time of TUG test(p=0.001). No significant within-group differences were observed in any of the variables in the control group (p˃ 0.05).Conclusion: The results of the present study showed that performing combined strength, aquatic, functional and balance exercises improve balance, joint proprioception, movement and walking performance in children. In addition, combined water and land exercises can improve the balance and proprioception of children with cerebral palsy and diplegia, and as a result the movement problems and falls of these children could be reduced, which is important for improving the health and lifestyle of these children. Therefore, prescribing this exercise training modality is recommended to trainers and therapists.